Whither systems medicine? - Apweiler, Rolf; Beißbarth, Tim; Berthold, Michael; Blüthgen, Nils; Burmeister, Yvonne; Dammann, Olaf; Deutsch, Andreas; Feuerhake, Friedrich; Franke, Andre; Hasenauer, Jan; Hoffmann, Steve; Höfer, Thomas; et al. (Experimental & molecular medicine, 2018)
New technologies to generate, store and retrieve medical and research data are inducing a rapid change in clinical and translational research and health care. Systems medicine is the interdisciplinary approach wherein physicians and clinical investigators team up with experts from biology, biostatistics, informatics, mathematics and computational modeling to develop methods to use new and stored data to the benefit of the patient. We here provide a critical assessment of the opportunities and challenges arising out of systems approaches in medicine and from this provide a definition of what systems medicine entails. Based on our analysis of current developments in medicine and healthcare and associated research needs, we emphasize the role of systems medicine as a multilevel and multidisciplinary methodological framework for informed data acquisition and interdisciplinary data analysis to extract previously inaccessible knowledge for the benefit of patients.
Gesehen am 02.07.2020